an Asian citrus psyllid parasitoid Tamarixia radiata (Waterston) (Insecta: Hymenoptera: Eulophidae) - Rajinder S. Mann; Lukasz L. Stelinski (EDIS)
EENY-475, a 5-page illustrated fact sheet by Rajinder S. Mann and Lukasz L. Stelinski, is part of the Featured Creatures collection. It describes this effective parasitoid of the Asian citrus psyllid, a vector for Huanglongbing disease in citrus — distribution, description, life cycle, hosts, and biological control. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.